Impact of UPF2 on the levels of CD81 on extracellular vesicles - Oh, Chaehwan; Mazan-Mamczarz, Krystyna; Gorospe, Myriam; Noh, Ji Heon; Kim, Kyoung Mi (Frontiers in Cell and Developmental Biology, 2024)
Extracellular vesicles (EVs) are involved in cell-to-cell communication. Following uptake, EV cargo molecules, including DNA, RNA, lipids, and proteins, influence gene expression and molecular signaling in recipient cells. Although various studies have identified disease-specific EV molecules, further research into their biogenesis and secretion mechanisms is needed for clinical application. Here, we investigated the role of UPF2 in regulating the biogenesis and components of EVs. Notably, UPF2 promoted the expression of CD81, a membrane protein marker of EVs, as UPF2 silencing decreased CD81 levels in EVs, both inside the cell and secreted. In contrast, the expression levels of CD63 increased, without altering the size or numbers of EVs. In addition, reducing UPF2 levels did not affect the total number of EVs but lowered production of CD81-positive EVs and reduced the efficiency of uptake by recipient cells. Collectively, our findings uncover a novel function for UPF2 in regulating the production of CD81 and changing EV properties.